2019
DOI: 10.1111/jcmm.14349
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals cell apoptotic signature modified by heparanase in melanoma cells

Abstract: Heparanase has been implicated in many pathological conditions, especially inflammation and cancer, attributed to its degradation of heparan sulfate, a crucial component maintaining the integrity of the extracellular matrix. By silencing the heparanase gene (HPSE) in MDA‐MB‐435s melanoma cells, we investigated the impact of this protein on gene transcription. Transcriptome sequencing yielded a list of 279 differentially expressed genes, of which 140 were up‐regulated and 239 down‐regulated. The 140 up‐regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
3
6
0
Order By: Relevance
“…Finally, we showed that heparanase increased cell survival following 5-FU treatment in MCF7 human breast cancer cells via the anti-apoptotic pathway. This finding is consistent with the known anti-apoptotic effect of heparanase in melanoma cells 35 . We assume that the different molecular mechanisms of chemoresistance, which were found to be induced by heparanase, contribute synergistically to its involvement in breast cancer survival following drug therapy.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, we showed that heparanase increased cell survival following 5-FU treatment in MCF7 human breast cancer cells via the anti-apoptotic pathway. This finding is consistent with the known anti-apoptotic effect of heparanase in melanoma cells 35 . We assume that the different molecular mechanisms of chemoresistance, which were found to be induced by heparanase, contribute synergistically to its involvement in breast cancer survival following drug therapy.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that silencing HPSE expression activated apoptosis and autophagy of HCC cells [16]. Signi cantly increased apoptotic cells upon HPSE silencing was also found in melanoma cells, mediated by the activation of caspase 3 pathway [17]. We showed here a negative correlation between the activities of cleaved caspase-3 and the level of HPSE, which indicated that the caspase-3 was probably involved in HPSE regulated cell apoptosis.…”
Section: Discussionsupporting
confidence: 67%
“…Significantly increased apoptotic cells upon HPSE silencing was also found in melanoma cells, mediated by the activation of caspase 3/PARP1 pathway [17]. We showed here a negative correlation between the activities of cleaved caspase-3/PARP and the level of HPSE, which indicated that the caspase-3/PARP was probably involved in HPSE regulated cell apoptosis.…”
Section: Discussionsupporting
confidence: 64%